Assessing the mitigation performance of building setback from street and the combination with roadside tree planting. (15th March 2022) - Tan, Zheng; Wang, Anqi; Morakinyo, Tobi Eniolu; Yung, Esther H.K.; Chan, Edwin H.W.
Abstract: Planning regulation measures are essential for creating healthy, liveable environments in highly developed cities like Hong Kong. Planning design strategies such as building setback and green cover have been proposed. However, the effectiveness of these strategies, especially the synergistic benefits of integrated application in real-world settings is a seldom-discussed topic. This study quantified the environmental benefits of building setback from street in high-density high-rise urban areas. In particular, the study considered the related dynamic changes in building height associated with the extra floor area incentive policy for encouraging building setback. Two streets were chosen as test cases from a highly developed, climate-sensitive urban districts. Numerical modeling was conducted in ENVI-met, and the accuracy in predicting wind speed and PET results was validated using real-site measurement data. Building setback and roadside tree planting work synergistically, and individual cooling efficiency was enhanced. 3-metre building setback with tree-planting demonstrates a similar mitigation outcome as the 6-m building setback scenario. Such an integrated method is able to create a comfortable microclimate in the heavily built urban areas. These findings point to the value of a balanced approach to sustainable urban development while maintaining density control. This study offers useful information for urban redevelopment and street improvement projects in high-density cities. Highlights: Improvements in PET mainly relate to increases in wind speeds. Building setback with tree planting creates comfortable thermal environments. Integrated and balanced design approaches are suggested in urban renewal. Case-by-case assessment is necessary when formulating site-specific strategies.